First Maritime Credit Corporation a total system documentation and design study - Abis, Sabrina Marie K.; Bongat, Jejomar O.; Cucio, Adriel Jireh V.; Madredia, Maila Rae O.
This Total Systems Documentation and Design study on First Maritime Credit Corporation was conducted between December 2013 and March 2014 upon the request of its mother company, Philippine Transmarine Carriers, Inc. The objectives of a Total Systems Documentation and Design study would be to document the existing processes behind the operations of the company, identify critical gaps and issues present in the system, and propose system-wide improvements to allow the company to perform better towards the achievement of its goal. In the context of First Maritime Credit Corporation, the goal is to minimize financial losses brought about by the failure to fully recover loans outstanding. The entire system of the company was divided into four subsystems, namely Application, Evaluation, Releasing and Collection. In the documentation of the existing system, the Service Blueprint framework was used in order to follow each loan transaction from its inception in the application stage, up to its conclusion in the collection stage. It was then concluded that critical gaps exist particularly in the Evaluation and Collection subsystems, as determined from a Root Cause Analysis conducted by the project team. The problem was then defined with respect to a performance metric defined by the Philippine Microfinance Standards published in 2002 by an inter-agency group headed by the Department of Finance. This is the Portfolio at Risk Ratio, which indicates the amount invested by the company in microfinance loans which is at risk of being defaulted, as determined from historical defaulting records. The ideal value for this is < 5%, and the maximum tolerable value is 20%. Presently, First Maritime Credit Corporation operates with a Portfolio at Risk Ratio of 31.85%. In addressing the goal, the project team has come up with a System Design Proposal encompassing the entire system of First Maritime Credit Corporation. The steps within the subsystems were predominantly retained, with the design recommendations being implemented within each step of the process. Published tools, frameworks, and good case practices from other microfinance institutions were referred to and adjusted in accordance with the operating realities of the company. All of the recommendations stated are expected to lead to an improvement not only on the subsystem, but the entire system of First Maritime Credit Corporation as a whole.